(untitled) (Journal of the College of Basic Education, 2025)
This research aims to identify the effect of the (penta Gram) strategy on the achievement of first-year middle school students in the dictation subject. To verify the research objective, the researcher formulated the following main null hypothesis: There is no statistically significant difference at the level (0.05) between the average scores of the experimental group students who study dictation according The researcher chose the community of Diyala Governorate to be his research sample, and chose from this community the (Jerusalem) Intermediate School from the center of Baqubah District, as the number of the sample reached (70) students, with (35) students in the experimental group, and (35) students in the control group, The researcher prepared appropriate teaching plans for the research sample and included preparing plans for both the experimental group and the control group. The research tool was the achievement test. At the end of the experiment, the researcher reached results, including: That the (penta Gram) strategy has a great impact in diversifying cognitive processing methods and in helping students interact in the classroom, which led to raising their level and their effective contribution to the lesson That teachers should use modern strategies in learning and teaching as much as possible and according to appropriate circumstances 1- The researcher suggested The following Conducting a similar study to determine the effectiveness of the (penta Gram) strategy in other educational and teaching stages for intermediate levels.